Engineered Nanostructured Materials for Ofloxacin Delivery - Nuti, Silvia; Fernández-Lodeiro, Javier; Del Secco, Benedetta; Rampazzo, Enrico; Rodríguez-González, Benito; Capelo, José L.; Silva, Vanessa; Igrejas, Gilberto; Poeta, Patrícia; Torres, Cármen; Zaccheroni, Nelsi; Prodi, Luca; et al. (Frontiers in Chemistry, 2018)
Antibiotic resistance is emerging as a growing worldwide problem and finding solutions to this issue is becoming a new challenge for scientists. As the development of new drugs slowed down, advances in nanotechnology offer great opportunities, with the possibility of designing new systems for carrying, delivery and administration of drugs already in use. Engineered combinations of the synthetic, broad-spectrum antibiotic ofloxacin, rarely studied in this field, with different types of silver, mesoporous silica-based and Pluronic/silica-based nanoparticles have been explored. The nanocarriers as silver core@silica mesoporous (AgMSNPs) and dye-doped silica nanoparticles functionalized with ofloxacin were synthesized and their antibacterial properties studied against S. aureus and E. coli. The best antibacterial results were obtained for the AgMSNPs nanosystem@ofloxacin for the strain S. aureus ATCC 25923, with MIC and MIB values of 5 µg/mL and 25 µg/mL, proving the efficacy and synergetic effect of the antibiotic and the Ag core of the nanoparticles.